Study and Fabrication of Virtual Shielded Metal Arc Welding Machine - Nguyen, Tien Duong (Old Journal, 2018)
The virtual shielded metal arc welding machine permits welding learner to perform the operations as in welding on the real shielded metal arc welding machine. This machine consists of machine structure and simulation software. The machine structure with the automatic screen turning, raising and lowering mechanism, allows the welding learner to be practiced the different positions with butt weld and fillet weld. The simulation software permits welding practice learner to select welding parameters, and it evaluates also the operations of learner via the skills of welding arc ignition, welding arc re-ignition, the maintenance of arc length, welding speed, weave pattern of holder and electrode angle.